A Contribution to the Accentual Characteristics in Svinica (Romania) - Lončar Raičević, Aleksandra R.; Jović, Nadežda D. (Collection of Papers of the Faculty of Philosophy in Priština, 2023)
This paper represents the continuation of phonetic-phonological research within the project “Research on the Culture and History of the Serbs in Romania”, which takes place under the auspices of the Center for Scientific Research and Culture of the Serbs in Romania. It is based on field research conducted during September 2022, in Serbian settlements in the Danube Gorge in Romania (Svinica). The analysis of accent characteristics—the inventory and distribution of prosodes in the speech of Svinica-revealed that it is a specific mixed speech type in which elements of the three-accent system are present, but also the process of simplification and liquidation of tonal oppositions and the appearance of an expiratory accent, which is characteristic of the speeches of Eastern Serbia. The analysis of the linguistic material presented in the paper supports the thesis concerning the autochthonous Serbian population in the Banat Gorge.